Transition in tobacco use stages and its related factors in a longitudinal study - Ahmad Khosravi; Mohammad Hassan Emamian; Hassan Hashemi; Akbar Fotouhi (Komiyama Printing Co. Ltd, 2018)
Abstract Objectives Considering the increase in the non-communicable diseases associated with tobacco use in recent decades in Iran, it is necessary to have a general view of the current condition. This study aimed to identify factors associated with tobacco use and to estimate the probability of a 5-year transition in the stages of tobacco use in an adult population. Methods In this study, 5190 people in the 40-64-year-old population of Shahroud (North East of Iran) were interviewed in 2009 and 2014 on tobacco smoking. The association of independent variables with tobacco smoking was evaluated using the population-averaged logit model. We calculated smoking transition probabilities from non-smoking to current smoking and past-smoking stages during a 5-year span. Results The prevalence of current tobacco smoking in 40-69-years age group was 11.1% (95% CI 10.3-12.0), 1% among women (95% CI 0.8-1.3) and 25.6% among men (95% CI 23.7-27.6). During this 5-year period, the probability of transition of a non-smoker to an overall current tobacco smoker was 2.3%. Meanwhile, 18.5% of the overall current tobacco smokers had changed into past smokers. Unemployed (OR = 2), male gender (OR = 53.9), widow/widowers (OR = 5.4), divorces (OR = 3.3), and high economic status (OR = 1.2) are associated to tobacco smoking. Conclusions Compared with the other studies, the prevalence of tobacco use in this population is low but transition rate of non-smokers into current smokers or past smokers is high. Conducting interventions on determinants of starting and quitting smoking and education and awareness raising on the risk and harms of smoking seems necessary.